2005
DOI: 10.4269/ajtmh.2005.72.119
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Mirazid in Comparison With Praziquantel in Egyptian Schistosoma Mansoni–infected School Children and Households

Abstract: This trial investigated the anti-schistosomal activity of mirazid in comparison with that of praziquantel in Schistosoma mansoni-infected Egyptian patients. The sample population was composed of 1,131 individuals (459 school children and 672 household members). Screening for S. mansoni was conducted using the standard Kato Katz technique. Four slides from a single stool sample were examined before treatment, and four slides per sample from stool samples obtained on three consecutive days were examined post-tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…[36][37][38][39][40] ARA seemed a far more promising schistosomicidal remedy than myrrh (Mirazid), which showed a low (10-15%) cure rate and low egg reductions in uncured individuals, regardless of the patients' ages or pre-treatment intensities of infection. [41][42][43] Despite that a 100% cure was reported after PZQ treatment of S. mansoni infections in eastern Sudan, 44 complete cures have seldom, if ever, been achieved in endemic areas after PZQ treatment. 45 Notably, 100% cure was also not achieved, even in children treated with a combination of PZQ and ARA, because two children still passed eggs.…”
Section: Discussionmentioning
confidence: 99%
“…[36][37][38][39][40] ARA seemed a far more promising schistosomicidal remedy than myrrh (Mirazid), which showed a low (10-15%) cure rate and low egg reductions in uncured individuals, regardless of the patients' ages or pre-treatment intensities of infection. [41][42][43] Despite that a 100% cure was reported after PZQ treatment of S. mansoni infections in eastern Sudan, 44 complete cures have seldom, if ever, been achieved in endemic areas after PZQ treatment. 45 Notably, 100% cure was also not achieved, even in children treated with a combination of PZQ and ARA, because two children still passed eggs.…”
Section: Discussionmentioning
confidence: 99%
“…These authors claimed that they cannot recommend the use of MZ for treatment of human schistosomiasis. MZ was also used for the treatment of S. mansoni infected Egyptian patients by Botros et al (2005) and very low cure rates were found (9.1% and 8.9% in S. mansoni infected school children and household members), compared with 62.5% and 79.6% cure rate in those treated with praziquantel, respectively. Barakat et al (2005) studied the effect of MZ on human schistosomiasis mansoni and found that the cure rate was very low after one treatment (15.6%) and much less (8.9%) by another treatment.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Botros et al (2005) found that MZ has a much lower cure rate, 9.1% and 8.9% in school children and household members, compared with 62.5% and 79.6%, in those treated with praziquantel respectively. Similarly, Barakat et al (2005) studied the effect of this drug on human schistosomiasis mansoni and found that the cure rate of MZ was 15.6% after one treatment and 8.9% after a second one.…”
Section: Introductionmentioning
confidence: 93%
“…The drug is safe and has a high efficacy against both trematodes and cestodes (9,11). Furthermore, there is evidence that treatment with praziquantel induces a change in the immune response that provides partial protection against schistosome infection, thus providing benefits that may extend beyond a transient reduction in levels of infection (21,40,42).…”
mentioning
confidence: 99%